Bank competition in Sub-Saharan African countries: Has anything changed in the light of 2007-2008 global financial crisis? - Steve Motsi; Oluseye Samuel Ajuwon; Collins Ntim (SPOUDAI - Journal of Economics and Business, 2018)
This paper investigated the changes in competitive behaviour of banks in sub-Saharan Africa, following the 2007/2008 global financial crisis. Using 481 bank-year observations from an unbalanced panel of 83 banks from six countries over the period 2008-2013. We employed the Panzar-Rosse model of firm competition, and found that the degree of competition among banks in Sub-Saharan Africa increased. This increase is due to the effect of reform/liberalisation policies, largely initiated in the pre-crisis era. The success that followed via the development of banking systems, nonetheless moderated at the onset of the 2007/2008 financial crisis. System instabilities, which were characteristic of a post-crisis period, exposed deficiencies in regulation and asymmetric incentives for bank management. A significant recalibration of prudential policies followed, as regulators sought to restore system stability, which again had an impact in altering competitive conduct of banks. Policymakers should continue to develop and promote policies geared towards the development of financial intermediation and improved competitive conduct of banks in sub-Saharan Africa.
Keywords: D41; D42; D43; E32; E44; F36; 330; bank competition; competitive behaviour; Panzar-Rosse model; H-Statistics; E-Statistics; sub-Sahara Africa